NUTRITIONAL AND PROBIOTIC QUALITY IN MAGGOT SUBSTRATE WASTE (KASGOT) FOR BROILER FEEDThis study aims to evaluate the nutritional quality and probiotic potential of Black Soldier Fly (BSF) maggot substrate waste or kasgot as an alternative feed ingredient - Dini Julia Sari Siregar; Warisman (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to evaluate the nutritional quality and probiotic potential of Black Soldier Fly (BSF) maggot substrate waste or kasgot as an alternative feed ingredient in broilers. The hypothesis of this study is that the addition of kasgot in the ration can increase the nutritional content as well as provide a probiotic effect that supports the health of the digestive tract of broiler chickens. The research was conducted using an experimental method with a Complete Random Design (RAL) consisting of 4 treatments and 5 replicates. The treatments provided include: P0 (control commercial feed), P1 (75% commercial feed + 25% cash), P2 (50% commercial feed + 50% cash), P3 (25% commercial feed + 75% cash), and P4 (100% cash). The parameters observed included the content of crude protein, crude fat, crude fiber, gross energy, and the potential of probiotic microbes in the cass. The results showed that P1 treatment provided the most optimal nutrient composition, with gross energy of 3078.34 cal/100g, crude protein 20.10%, and crude fat 5.35%. Giving kasgot at the level of 25% is considered more effective than higher levels because it maintains the nutritional balance of the ration and supports the function of natural probiotics for broilers. In conclusion, kasgot has the potential to be an alternative feed ingredient and a source of probiotics that can be used in the formulation of broiler chicken rations at a substitution level of 25%.